Integrative metagenomic and metabolomic profiling identifies gut microbial and metabolite signatures associated with lymph node metastasis in pancreatic cancer - Li, Pengyu; Wang, Mingfei; Zhang, Hanyu; Gao, Xingyu; Chen, Lixin; Chen, Haomin; Xu, Qiang; Chen, Weijie; Liu, Wenjing; Dai, Menghua (Frontiers in Microbiology, 2025)
BackgroundLymph node metastasis (LNM) is a prognostic factor in pancreatic cancer. The association between the gut microbiota and LNM remains unexplored. This study aimed to characterize the gut microbiota and metabolomic profiles associated with LNM and to investigate their potential as predictive biomarkers.MethodsFecal samples from pancreatic cancer patients undergoing surgery were analyzed using metagenomic sequencing and untargeted metabolomics. The patients were categorized into LNM and non-LNM (NLNM) groups. Differential microbiome taxa were analyzed using the DESeq2 package. Random forest predictive models were developed based on metagenomic and metabolomic data, with performance assessed using leave-one-out cross-validation (LOOCV).ResultsA total of 26 patients with LNM and 29 patients without LNM were included. Principal coordinates analysis (PCoA) revealed significant differences in microbiota composition between the two groups (Anosim, p = 0.047). The absolute counts of Ruminococcus gnavus and Blautia wexlera were significantly decreased in LNM. Tryptophan-derived metabolites, indole-3-lactic acid (3-ILA) and indole-3-acrylic acid (3-IA), were downregulated in LNM. Functional pathway analysis showed downregulation of tryptophan metabolism in LNM, while cancer-related pathways were upregulated. Correlation analysis revealed a significant positive association between Ruminococcus gnavus and 3-ILA/3-IA levels. Moreover, Ruminococcus gnavus was positively correlated with CD8+ T cells. Predictive models based on the gut microbiota and metabolites distinguished LNM from NLNM, with AUC values of 0.854 and 0.940, respectively.ConclusionThe gut microbiota and metabolites exhibit significant alterations during lymph node metastasis in pancreatic cancer, especially Ruminococcus gnavus, Blautia wexlera, and tryptophan metabolites (3-ILA and 3-IA). Gut microbial and metabolite signatures may serve as potential non-invasive biomarkers for predicting LNM in pancreatic cancer. Further functional validation is required to determine whether and how the gut microbiota and metabolites may mediate lymph node metastasis.